Adsorption of Azobenzene on Hexagonal Boron Nitride Nanomesh Supported by Rh(111) - Szitás, Á. (J Phys Chem C Nanomater Interfaces, 2020)
[Image: see text] Adsorption properties of azobenzene, the prototypical molecular switch, were investigated on a hexagonal boron nitride (h-BN) monolayer (“nanomesh”) prepared on Rh(111). The h-BN layer was produced by decomposing borazine (B(3)N(3)H(6)) at 1000–1050 K. Temperature-programmed desorption (TPD) studies revealed that azobenzene molecules adsorbed on the “wire” and “pore” regions desorb at slightly different temperatures. Angle-resolved high-resolution electron energy loss spectroscopy (HREELS) measurements demonstrated that the first molecular layer is characterized predominantly by an adsorption geometry with the molecular plane parallel to the surface. Scanning tunneling microscopy (STM) indicated a clear preference for adsorption in the pores, manifesting a templating effect, but in some cases one-dimensional molecular stripes also form, implying attractive molecule–molecule interaction. Density functional theory (DFT) calculations provided further details regarding the adsorption energetics and bonding and confirmed the experimental findings that the molecules adsorb with the phenyl rings parallel to the surface, preferentially in the pores, and indicated also the presence of an attractive molecule–molecule interaction.